2009
DOI: 10.1143/jpsj.78.114716
|View full text |Cite
|
Sign up to set email alerts
|

Pair-Hopping Mechanism for Layered Superconductors

Abstract: We propose a possible charge fluctuation effect expected in layered superconducting materials. In the multireference density functional theory, relevant fluctuation channels for the Josephson coupling between superconducting layers include the interlayer pair hopping derived from the Coulomb repulsion. When interlayer single-electron tunneling processes are irrelevant in the Kohn-Sham electronic band structure calculation, the two-body effective interactions stabilize a superconducting phase. This state is als… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…4,5) However, several theoretical studies have shown that simple application of the strong-coupling theory for the electron-phonon mediated superconductivity fails in explaining the superconductivity of iron arsenides. 6) This problem can be solved by conducting a first-principles electronic structure calculation using a technique 7) beyond local density approximation (LDA). In this new theory, the calculation starts from an analysis of the results by LDA or generalized gradient approximation (GGA), taking fluctuation effects due to Coulomb repulsion into consideration of the simulation.…”
Section: Introductionmentioning
confidence: 99%
“…4,5) However, several theoretical studies have shown that simple application of the strong-coupling theory for the electron-phonon mediated superconductivity fails in explaining the superconductivity of iron arsenides. 6) This problem can be solved by conducting a first-principles electronic structure calculation using a technique 7) beyond local density approximation (LDA). In this new theory, the calculation starts from an analysis of the results by LDA or generalized gradient approximation (GGA), taking fluctuation effects due to Coulomb repulsion into consideration of the simulation.…”
Section: Introductionmentioning
confidence: 99%
“…If we have two-dimensionality in the doped band, the inter-layer pair-hopping mechanism [17] may work. For a slightly doped two-dimensional band of a semiconductor, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, when UD and overdoped (OD) films of the La-214 cuprates are piled up [26], there can be an enhancement of the superconducting transition temperature to above that in the bare films. These observations suggest that interlayer coupling [57][58][59][60][61][62] may play a role and the ground states in monolayered and multilayered cuprates are unlike [63][64][65][66][67][68][69][70][71][72][73][74][75].…”
Section: Introductionmentioning
confidence: 99%